Cell engineering by the internalization of bioinstructive micelles for enhanced bone regeneration - Santo, Vitor E. (2015)
To direct precursor cells toward the osteoblastic lineage, by using an intracellular nanocarrier releasing dexamethasone. Materials & methods: Biodegradable gelatinbased micelles entrapped dexamethasone (dex-micelles). Internalization efficiency and biocompatibility of dex-micelles and their potency for in vitro osteogenic differentiation and in vivo bone regeneration were assessed. Results: Dex-micelles were internalized by rat bone marrow mesenchymal stem cells and demonstrated a pH-responsive release profile and an enhancement of 2D and 3D in vitro osteogenic differentiation. In vivo implantation of gelatin scaffolds seeded with rat bone marrow mesenchymal stem cells precultured for 24 h with dex-micelles promoted a significant enhancement of de novo bone formation in a rat ulna defect, in a dose-dependent manner. Conclusion: The proposed intracellular delivery system is a powerful tool to promote bone regeneration.